PENGELOLAAN PAJAK HOTEL DAN PAJAK RESTORAN DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) - Saputra, Fahri; Heriyanto, Meyzi; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2019)
Management of Hotel Taxes and Restaurant Taxes in the Context of IncreasingRegional Original Income. This study aims to determine and analyze the management of hoteltaxes and restaurant taxes by the Regional Office of Financial and Asset Management Revenue inSiak Regency in order to increase Regional Original Revenue. This study uses a qualitativedescriptive method approach. Primary data was obtained directly through interviews from keyinformants, namely the Head of DPPKAD, Secretary of DPPKAD, Head of PAD and BalancingFunds, Section Head of Data Collection and Determination, Head of Billing and Receipt ofReceipts, and Head of Objection Examination Section and Legislation. Secondary data is obtainedfrom research documents. The results showed that the Siak Regency Government had made effortsto improve hotel tax management and restaurant taxes through intensification of hotel tax sourcesand restaurant taxes as well as extensification of hotel tax sources and restaurant taxes, but not yetoptimal as cash inflows area.